The future of global sugar markets: Policies, reforms, and impact. Proceedings of a Public Conference. - Orden, David; Bureau, Jean-Christophe; Gohin, Alexandre; Guindé, Loïc; Millet, Guy; Brandão, Antônio Salazar P.; Haley, Stephen; Wagner, Owen; Sandrey, Ron; Vink, Nick (International Food Policy Research Institute, 2008)
Sugar is one of the most highly protected agricultural commodities worldwide. This protection depresses trade opportunities and the prices received by exporters without preferential market access. For this reason, dialogues about sugar policy are often polarized and short sound bites caustic. Yet today’s sugar markets are being driven by a complex array of dynamic and emerging supply, demand, and policy forces that need to be understood. A number of these forces have the potential to reshape the global market scene. Recent sugar policy reforms in the European Union (EU) have received little attention in North America but may turn the EU into a net importer, with substantial compensation paid to its farmers and displaced processing facilities. High oil prices and the related ethanol boom place Brazil at the fulcrum of new market developments. In the United States, corn sweetener and sugar markets are being integrated with Mexican markets under the North American Free Trade Agreement (NAFTA), raising the question of whether the EU reforms provide a template for new policies. And among developing countries in Africa and elsewhere there are low-cost producers that would benefit from more open trade but others who would be disadvantaged by the loss of preferential markets. This discussion paper presents the proceedings of a one-day conference that served as a forum for the discussion of these and other critical issues affecting global sugar markets, policies, and reform options. The conference was attended by 60 representatives of governments, research institutions, producers and processors from the sugar sector, and other groups interested in sugar markets and policies. The four papers were presented by internationally recognized experts from the EU, Brazil, the United States, and South Africa. Discussion openers and general discussion at the conference added further policy insights, and the papers were edited and revised after the conference to reflect the dialogue that had occurred.